(untitled) (Global Journal of Science Frontier Research, 2012)
Thin films (average thickness 1132, 2236, and 3785 nm) of polystyrene with a hydroxyl end group, PSOH (Mw= 70345 g.mol) were supported on SiO 2 monolith disks (thickness 0.2, 0.4, and 0.6 cm) to measure its thermal conductivity response using the Lee’s Disk method. The various analyses were carried out over a 40 minute period at intervals of 5 minutes, at a temperature range of 20 to 110°C, as a function of PSOH film and monolith disk thickness. As a result, an extremely low thermal conductivity was determined in reference to the individual materials. Additionally, the thermal conductivity was unaltered as a result of the variation of the film and monolith thickness. In contrast, the hardness and ductile behavior were increased by increasing the thickness of the PSOH film. As a result of this, monoliths with a PSOH film of 3782 nm thicknesses (and load of 100 gf) were considered materials of intermediate hardness (value of 31.5720 GPa). In addition, FTIR was the technique employed to establish the PSOH and SiO 2 monolith structures.